Does the Black-White mental health paradox persist across U.S. geographical regions? - Christy L. Erving; Lacee A. Satcher; Shania Montúfar; Courtney S. Thomas Tobin (SSM - Mental Health)
Purpose: The “Black-White mental health paradox” refers to the epidemiological pattern whereby Black Americans experience similar, and often lower, rates of psychiatric disorders relative to their White counterparts despite their greater exposure to stressors and societal-level racism. The aim of this study is to examine the extent to which the Black-White mental health paradox is observed within four U.S. geographical regions: Midwest, Northeast, South, and West. Methods: A sample of Black and White Americans was drawn from the National Comorbidity Survey-Replication (NCS-R) and the National Survey of American Life (NSAL). Racial patterns of disorder were examined before and after adjusting for other sociodemographic characteristics (e.g., education, employment status, marital status, sex, age). Logistic regression analysis estimated relative odds of past-year mood, anxiety, substance use, and any disorder among Black and White adults within each region. Results: Evidence of the paradox was most prominent in the U.S. South region. Black Southerners experienced lower odds of mood, anxiety, and any disorders relative to their White Southern counterparts. Black individuals in the Northeast and West also had lower odds of any disorder vis-a-vis their White counterparts. By contrast, Black Americans in the Midwest experienced elevated odds of mood disorders compared to White Midwesterners; this racial pattern, however, dissipated after adjusting for sociodemographic characteristics (e.g., education, employment). Conclusion: Mental health intervention and prevention programs should address the elevated risk of mood disorder among Black Americans living in the Midwest, in part by ameliorating racial inequalities in access to education, employment, and other economic resources.